2021
DOI: 10.24251/hicss.2021.492
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with Machines: Conversational Agents with Personality and the Role of Extraversion

Abstract: Communication with conversational agents (CA) has become increasingly important. It therefore is crucial to understand how individuals perceive interaction with CAs and how the personality of both the CA and the human can affect the interaction experience. As personality differences are manifested in language cues, we investigate whether different language style manifestations of extraversion lead to a more anthropomorphized perception (specifically perceived humanness and social presence) of the personality b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…In further research, the concrete influencing components of an interaction are also to be identified in order to develop concrete guidelines and design patterns for the active design of interactions on this basis. In addition, the technologies currently discussed in IS and their applications such as emotion recognition , personality mining (Ahmad et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…In further research, the concrete influencing components of an interaction are also to be identified in order to develop concrete guidelines and design patterns for the active design of interactions on this basis. In addition, the technologies currently discussed in IS and their applications such as emotion recognition , personality mining (Ahmad et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…In further research, the concrete influencing components of an interaction are also to be identified in order to develop concrete guidelines and design patterns for the active design of interactions on this basis. In addition, the technologies currently discussed in IS and their applications such as emotion recognition (Meyer et al, 2019), personality mining (Ahmad et al, 2021), AI or chatbots are to be examined in relation to the Value in Interaction Model. The aim is to find out how these technologies have to be integrated into the interactions between retailers and customers in order to generate value and what contribution they make to the PRQ in comparison to each other.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in paraverbal language, cues such as speech rate range, loudness or fundamental frequency distinguish submissive from dominant individuals [35]. On all three communication levels, such language cues can be used to help imbue CAs with personalities, in order to sustain more human-like interactions with people [13,14,15]. A combination of these linguistic cues can further help portray a specific CA personality: as some contexts, for example in mental health care, require CAs to have a more emphatic and agreeable personality rather than a neurotic personality.…”
Section: Personality and Linguistic Cuesmentioning
confidence: 99%
“…In recent years, researchers have specifically focused on designing human-like CAs by giving them a personality: first, to propose more complete cognitive models of CAs, and second, to propose CAs capable of sustaining more human-like interactions with people [13,14,15]. The Big Five model of personality has emerged as a standard in psychology, with research over the last fifty years systematically documenting correlations between personality traits and a wide range of behaviors [16,17,18].…”
Section: Introductionmentioning
confidence: 99%